The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3310/hsdr06140
|View full text |Cite
|
Sign up to set email alerts
|

Variation in outcome of hospitalised patients with out-of-hospital cardiac arrest from acute coronary syndrome: a cohort study

Abstract: Background Each year, approximately 30,000 people have an out-of-hospital cardiac arrest (OHCA) that is treated by UK ambulance services. Across all cases of OHCA, survival to hospital discharge is less than 10%. Acute coronary syndrome (ACS) is a common cause of OHCA. Objectives To explore factors that influence survival in patients who initially survive an OHCA attributable to ACS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 130 publications
0
15
0
Order By: Relevance
“…Because of the limitations of ICD‐10 coding, we were unable to accurately differentiate shockable (VT or VF) versus nonshockable (bradyarrhythmia or pulseless electrical activity) rhythms during CA. However, previous data from a similar cohort suggested that 89.6% of patients who have out‐of‐hospital CA in the context of ACS have VT or VF as the presenting rhythm, 1 which provide the basis for our assumption that the vast majority of CAs at the time of ACS in our study are attributed to VAs.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Because of the limitations of ICD‐10 coding, we were unable to accurately differentiate shockable (VT or VF) versus nonshockable (bradyarrhythmia or pulseless electrical activity) rhythms during CA. However, previous data from a similar cohort suggested that 89.6% of patients who have out‐of‐hospital CA in the context of ACS have VT or VF as the presenting rhythm, 1 which provide the basis for our assumption that the vast majority of CAs at the time of ACS in our study are attributed to VAs.…”
Section: Discussionmentioning
confidence: 58%
“…A minority of acute coronary syndrome (ACS) patients who survive to hospital admission are associated with ventricular arrhythmia (VA), a subset of which cause cardiac arrest (CA). 1 Acute myocardial ischemia leads to a series of progressive electrophysiological changes at the cellular level that predispose to VA, 2 although it remains unclear why only a minority of patients with ACS develop VA, whereas the vast majority do not. 3 …”
mentioning
confidence: 99%
“…Finally, transfer to a cardiac arrest centre is thought to improve survival following OHCA but a potential effect size has not been clearly defined. 28,29 In our study, bypass of the nearest hospital in favour of a cardiac centre was a relatively common prehospital critical care intervention. However, the receiving hospital for patients in the ALS group was a cardiac arrest centre in nearly half of the patients transferred, thereby diluting a potentially small to moderate effect of prehospital critical care.…”
Section: Explanations Of Research Findingsmentioning
confidence: 71%
“…Nevertheless, there is much variability in longterm prognosis for patients with acute coronary syndrome who survive to be discharged from the hospital. 7,8 Some studies have been conducted in Iran to determine the survival rate in different provinces, but none of them has been population-based, considering the whole country using MI registry data and type of drugs prescribed at the time of discharge. Therefore, this retrospective cohort study was designed to estimate short-and long-term survival rates in MI patients and their contributing factors and medications prescribed at the time of discharge in patients with the first attack of MI in the Islamic Republic of Iran.…”
Section: Introductionmentioning
confidence: 99%